Main indicators of the credit organizations of the Russian Federation: vectors of changes - T. V. Grishina (Статистика и экономика, 2017)
Credit organizations are a crucial part of the credit-monetary relations, greatly infl uencing the development of the Russian economy. In recent years, changes in the structure of the banking system and the profi tability of operations conducted by banks. Analysis of the functioning of the system shows a reduced role of banking indicators in the formation of the Russian GDP. The process of credit expansion stopped. To determine the vectors of development of credit institutions is not enough to conduct traditional statistical studies of the dynamics of the institutional structure of the banking system, since it is possible to obtain erroneous conclusions regarding the efficiency of banks in the economy. You must take into account a broader set of indicators, which allows to make more accurate conclusions about the vectors of change in the banking business in General. By mapping levels of the time series in the article the analysis of structural shifts in the activities of Russian credit organizations. Examines the spatial distribution of the credit institutions, are allocated in the regions with the highest activity of credit institutions and regions where the development potential of the banking sector implemented is not enough. The tendencies in the banks talking about displacement vectors of business development from the credit expansion in the direction of the Commission operations. The decline of profi tability of foreign exchange transactions and interest margin increases competition for customers, winning banks which can only support the broadest range of services with possibility of remote access. According to the analysis conclusions are made about the continuation of the trend of reducing the number of credit institutions with the growth of volumes of payments made by Bank customers through electronic orders. Given the positive assessment of the prospective transition to a gradation of banks with basic and universal licenses, which will enable the variability of the supervision for small and medium-sized banks in their competition with the largest credit organizations.